Cooperative learning with QR codes technology: enhancing cognitive achievement and attitudes among students - Rakha, Ahmed Hassan (Frontiers in Education, 2025)
IntroductionIntegrating quick response (QR) codes into cooperative learning may streamline access to multimedia, reduce extraneous cognitive load, and improve learning outcomes in technology-rich courses.MethodsA quasi-experimental single-group, repeated-measures design was used with 30 regularly attending undergraduates in “Technology in Sports.” Students completed a cognitive test at pre-, post-, and 1-month follow-up; attitudes were collected post-course via a validated Likert instrument. Instruction employed five cooperative strategies (Think–Pair–Share, Timed Pair Share, Three-Step Interview, Jigsaw, Case Study) supported by QR-linked resources.ResultsRepeated-measures ANOVA showed significant gains from pre- to post-test with retention at follow-up (η² = 0.89, α = 0.05). Post vs. follow-up differences were nonsignificant, indicating maintenance. Power analysis indicated 1 − β = 1.00. Attitude scores were positive across cognitive, emotional, and behavioral dimensions.DiscussionQR-supported cooperative learning improved and sustained cognitive achievement and elicited favorable student attitudes. Thoughtful instructional design, teacher readiness, and high-quality resources appear critical to effectiveness.ConclusionEmbedding QR technology within cooperative learning is a feasible, learner-centered approach that enhances outcomes and attitudes in higher-education sport-technology courses.